Modern Methods of Creating Casting Model Kits - M. L. Kalinichenko; L. P. Dolgiy; S. L. Rovin; V. A. Kukareko; U. A. Kalinichenko (Литьë и металлургия, 2018)
The article presents some information about creation of model kits and core equipment for the manufacture of molds and rods of cold-hardening sand-clay mixtures in the individual, serial and mass production of castings of ferrous and non-ferrous metals. There was analyzed their constituent materials and investigated a number of mechanical properties of the binding components for their attachment. Was shown the analysis of adhesive compositions of the world’s leading manufacturers, used for the manufacture of high-strength model sets by 3D milling methods.